2004
DOI: 10.1093/ndt/gfh528
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between somatostatin analogues and ACE inhibitor in the NOD mouse model of diabetic kidney disease

Abstract: SST analogues exert beneficial effects in most parameters of diabetic kidney disease to the same extent as the ACEi. Enalapril treatment had no effect on renal hypertrophy and did not cause a significant decrease in mesangial type IV collagen deposition. A synergistic effect of combined SST-ACEi therapy could not be shown in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
11
1
Order By: Relevance
“…GH replacement in men with abdominal obesity can diminish the negative metabolic consequences of visceral obesity [22], suggesting that low levels of this hormone are important for the metabolic aberrations in obese type 2 diabetic patients [23]. In our study we showed that the addition of a GH antagonist (somatostatin) did not affect any of the renal parameters (hypertrophy, hyperfiltration and albuminuria), contrary to previous reports on beneficiary effects of GH antagonists in type 1 diabetes mellitus [13], thus supporting the concept that no further suppression of GH is indicated in type 2 diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…GH replacement in men with abdominal obesity can diminish the negative metabolic consequences of visceral obesity [22], suggesting that low levels of this hormone are important for the metabolic aberrations in obese type 2 diabetic patients [23]. In our study we showed that the addition of a GH antagonist (somatostatin) did not affect any of the renal parameters (hypertrophy, hyperfiltration and albuminuria), contrary to previous reports on beneficiary effects of GH antagonists in type 1 diabetes mellitus [13], thus supporting the concept that no further suppression of GH is indicated in type 2 diabetes mellitus.…”
Section: Discussioncontrasting
confidence: 99%
“…Immunoassays for serum GH Serum GH was measured by RIA, as previously described [13], using a specific polyclonal antibody. The sensitivity of the method was 0.04 ng murine GH per tube; the CVs for tested sera at 13.9 and 201.1 μg/l were 13.6 and 5.9%, respectively.…”
Section: Animal Experimentationmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6]12] Increased circulating growth hormone levels have been reported in rodents with diabetic nephropathy. [13] In some experimental studies, growth hormone receptor antagonist's treatment protected the animals against development of renal changes. [14,15] Although it is well known that ghrelin is a growth hormone secretagogue, there have been no studies that investigate the relationship between increased ghrelin and growth hormone in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%